1981
DOI: 10.1520/jte11553j
|View full text |Cite
|
Sign up to set email alerts
|

Multiaxial Fatigue: A Survey of the State of the Art

Abstract: This paper surveys the current state of knowledge concerning multiaxial fatigue. Developments are presented in chronological order and are discussed so as to supplement existing reviews in this field. Emphasis is placed primarily on the criteria or methods of evaluation of fatigue strength under general multiaxial loading at room temperature. The survey indicates that the early development of the criteria was based on extensions of static yield theories to fatigue under combined stresses. These are stress-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

1985
1985
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…1 Several reviews of these models can be found in the literature. [2][3][4][5][6] In general terms, critical plane stress-based criteria are designed to assess the fatigue behavior considering an infinite fatigue life approach, where loading histories and material properties are taken into account to determine whether or not fatigue failures are to be expected. In this case, attention is focused on guaranteeing a good margin of safety against failure by admitting loading conditions in proximity with the fatigue resistance limit, above which fatigue failure can occur and below which fatigue life extends over a very high number of cycles (theoretically infinite).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Several reviews of these models can be found in the literature. [2][3][4][5][6] In general terms, critical plane stress-based criteria are designed to assess the fatigue behavior considering an infinite fatigue life approach, where loading histories and material properties are taken into account to determine whether or not fatigue failures are to be expected. In this case, attention is focused on guaranteeing a good margin of safety against failure by admitting loading conditions in proximity with the fatigue resistance limit, above which fatigue failure can occur and below which fatigue life extends over a very high number of cycles (theoretically infinite).…”
Section: Introductionmentioning
confidence: 99%
“…The large number of models belonging to this approach can be typically classified into four divisions based on empirical equivalent stress, stress invariants, average stress, and critical plane stress 1 . Several reviews of these models can be found in the literature 2–6 …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, fatigue damage criterions have been adopted to investigate the fatigue failure mechanism. Several multiaxial fatigue criterions have been investigated in this study using the 3D multiaxial stress state condition . The orientation of the planes where the fatigue cracks initiate cannot be explicitly obtained in some cases such as in the stress invariant criteria, which is a distinguishable factor from uniaxial fatigue criterions.…”
Section: Introductionmentioning
confidence: 99%
“…Several multiaxial fatigue criterions have been investigated in this study using the 3D multiaxial stress state condition. [17][18][19][20][21] The orientation of the planes where the fatigue cracks initiate cannot be explicitly obtained in some cases such as in the stress invariant criteria, which is a distinguishable factor from uniaxial fatigue criterions. Therefore, critical plane-based criterions are applied in this study to investigate the orientations of the planes for initiated cracks.…”
Section: Introductionmentioning
confidence: 99%
“…Multiaxial fatigue of materials and structures has been investigated for about 120 years and many different mathematical models of the limit state of strength have been formulated. At present, we know more than 60 criteria of fatigue strength under multiaxial loading [2][3][4]. There are stress-, strain-, and energy-based fatigue failure criteria, but there are no universal criterion for different structural materials and loading conditions [4].…”
Section: Introductionmentioning
confidence: 99%